Caracterización de las propiedades mineralógicas y mecánicas de las arcillas presentes en la parroquia Casanga, cantón Paltas, provincia de Loja, para el aprovechamiento en la industria cerámica. - Chuncho Salas, Cinthya Isabela (2024)
The clays present in the parish of Casanga, canton Paltas, province of Loja constitute an important resource that to date has not been properly investigated, resulting in a lack of understanding of the potential of this material. Despite the fact that the parish has several economic, social and environmental problems and that the diversification of productive activities is proposed as a measure to improve the living conditions of the inhabitants, there has been no investment in generating information that explores the possibilities of the sector, which implies knowing its non-metallic mineral resources, which is why the present work characterizes such a valuable resource as clays, defining the type of clays analyzed, as well as their chemical, mechanical, ceramic and mineralogical properties. The data provided for four sampling points include qualitative and mostly quantitative characteristics with their respective interpretation, this includes values of moisture content, specific gravity, plasticity, granulometry, linear shrinkage, color, water absorption, pH, chemical composition and mineralogical phases, some tests performed on natural, dry or fired samples, depending on the property. Based on the results, the material is classified according to its clay minerals "Kaolin Group", according to its chemical composition "Non-marly plastic clays" and according to its industrial properties "Clays for bricks". The execution of this project results in an information base that contributes to the knowledge of the resources of the sector and implies a starting point for a possible industry that will benefit not only the community of the sector, but also its surroundings and the ceramic construction industry that is developed in the province of Loja. Keywords: clays, Casanga, proprieties, mineralogy, industry, resource.